Alkaloids Isolated from Dehaasia candolleana (Meisn.) Kosterm - A. Hadi, A. Hamid; Ropi Mukhtar, Mat '; Choon Wee, Khoo '; Syed Abd. Azziz, Saripah Salbiah (Malaysian Journal of Science, 2008)
Three alkaloids were isolated from the bark of Dehaasia candolleana (Meisn.) Kosterm; one morphinandienone, (-)-sebiferine 1 and two bisbenzylisoquinoline alkaloids namely (-)- 0,0-dimethylgrisabine 2 and grisabine 3. Structural elucidations of these alkaloids were performed using spectroscopic methods notably ill, '3C-NMR (1D and 2D) and compared with reported data. Alkaloids 1 and 2 exhibited potent in vitro antiplasmodial activities to two strains of P. falciparum; D10 strain (sensitive strain) and Gombak A isolate (resistant strain)